2017
DOI: 10.1007/s00467-017-3686-4
|View full text |Cite
|
Sign up to set email alerts
|

Life with one kidney

Abstract: Life with a solitary functioning kidney (SFK) may be different from that when born with two kidneys. Based on the hyperfiltration hypothesis, a SFK may lead to glomerular damage with hypertension, albuminuria and progression towards end-stage renal disease. As the prognosis of kidney donors was considered to be very good, having a SFK has been considered to be a benign condition. In contrast, our research group has demonstrated that being born with or acquiring a SFK in childhood results in renal injury before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 96 publications
1
36
0
2
Order By: Relevance
“…The dysregulation of BP mainly for systolic values in our cohort should be consistent with the hypothesis of extracellular fluid expansion [23]. Therefore, avoiding excessive salt intake, which is a common characteristic of Western diets and is implicated in cardiovascular disease, appears to be indicated from childhood in children with CSK, as also highlighted in two recent reviews [24,25].…”
Section: Discussionsupporting
confidence: 87%
“…The dysregulation of BP mainly for systolic values in our cohort should be consistent with the hypothesis of extracellular fluid expansion [23]. Therefore, avoiding excessive salt intake, which is a common characteristic of Western diets and is implicated in cardiovascular disease, appears to be indicated from childhood in children with CSK, as also highlighted in two recent reviews [24,25].…”
Section: Discussionsupporting
confidence: 87%
“…97 The current fixed GFR threshold of 60 ml/min per 1.73 m 2 not only results in overdiagnosis of CKD in the older adults, it may also lead to missed diagnoses of CKD in younger individuals who lack overt signs of kidney damage and have a GFR above the fixed threshold of 60 ml/min per 1.73 m 2 but below the lowest percentile for their age. This group may include young people with low-nephron endowment, such as individuals born with a single kidney, 145 those born preterm 146 or at a low birth weight, patients with Down syndrome, 147 or young people with a past history of treatment with nephrotoxic drugs. 148 Such individuals are at risk for developing progressive CKD over their remaining lifetime, and may experience associated comorbidities and adverse events, including an increase in mortality.…”
Section: Potential Effect Of An Updated Definition Of Ckdmentioning
confidence: 99%
“…Despite these discrepancies, collectively in these studies it was shown that a congenital SFK does incur a greater predisposition for hypertension and kidney dysfunction later in life. However, there is a need for large long-term follow up studies beyond adolescence in individuals with a congenital SFK, as kidney dysfunction may develop later in life ( Kolvek et al, 2014 ; Schreuder, 2017 ). It would be highly desirable to determine at diagnosis of SFK, which children have a poor prognosis and for this, accurate and sensitive biomarkers need to be identified.…”
Section: Clinical Outcomesmentioning
confidence: 99%